A Comparative Analysis of Labor Rights Reporting on Financial Crisis - Salawati, Sahari; Noradiva, Hamzah; Mohamat Sabri, Hassan; Ridhuan, Che Abdul Rahman; Mohd Waliuddin, Mohd Razali (UMT, 2017)
Labor rights reporting as part of human capital disclosure is an important area of corporate reporting as it highlights part of the corporate’s social interest. This paper emphasizes the international issues of financial crisis by analyzing the differences in the labor rights disclosure before and after the crisis. Hence, drawing upon legitimacy theory of organizations, this study posits that in an attempt to legitimize corporate activities, the corporate would practice different disclosure strategies in different situations. To analyze the items disclosed, content analysis technique and the comparative analysis were used in order to significantly measure the difference of labor rights disclosure during and soon after the global financial crisis. However, the results revealed that there were no significant differences in labor rights reporting on such selected periods. This study offers an insight on the international issues of financial crisis and its significant towards labor rights reporting whereby it could guide the corporation regarding to the voluntary disclosure specifically on the labor rights during financial crisis